Occupational hazards and health cost of women cotton pickers in Pakistani Punjab. (December 2016) - Bakhsh, Khuda; Ahmad, Naeem; Kamran, M.; Hassan, Sarfraz; Abbas, Qasir; Saeed, Rashed; Hashmi, M.
Abstract Background Farm workers and female cotton pickers are exposed to residual impacts of pesticide use in cotton production, in addition to dust, ultraviolet radiation, etc. Cotton picking causes various health hazards among cotton pickers with varied health cost. A soil bacterium known asBacillus thuringiensis (Bt) is incorporated in cotton seed through genetic modification and it has resistance against certain bollworms of cotton. So it is considered that Bt cotton fields have less pesticide exposure compared to non-Bt cotton fields. This study was designed to examine and compare the impacts and health cost of cotton picking among female cotton pickers working in Bt and non-Bt cotton fields. Methods The study used the data collected from Vehari district of Pakistani Punjab. Health hazards and associated health cost of the respondents involved in Bt cotton picking were compared with those who harvested non-Bt cotton. Comparative use of the personal protective measures among those respondents was also examined. Health cost function and its determinants were analyzed using ordinary least square method. Results Findings of the study showed that 61 % cotton pickers from Bt cotton households reported one or more health effects of pesticide during picking season whereas this percentage for non-Bt cotton households was 66 %. Health impacts included skin problems, headache, cough, flu/fever, eye irritation and sleeplessness, however, percentage of these health impacts was comparatively higher among non-Bt cotton households. Health cost from exposure to pesticide use in cotton was US$ 5.74 and 2.91 per season for non-Bt cotton and Bt cotton households, respectively. Education, picking in Bt cotton fields and preventive measures were significantly related with health cost. Conclusion Cotton pickers working in Bt cotton fields are found to have less occupational health hazards compared to those working in non-Bt cotton fields. Thus generating awareness among cotton pickers for adopting precautionary measures during harvesting and the use of Bt cotton seed can result in a decline in the ill-effects of cotton picking.